Accurate acetabular cup placement using a smartphone-based digital alignment guide in total hip arthroplasty - Yuki Teranishi; Yusuke Okanoue; Junpei Dan; Dai Ohira; Masahiko Ikeuchi (Journal of Joint Surgery and Research)
Purpose: Successful total hip arthroplasty (THA) requires accurate positioning of the acetabular cup. Although computed tomography (CT)-based navigation technology enables more accurate placement, most navigation systems are bulky, expensive, and often inaccessible due to cost and complexity. The purpose of this study was to introduce a smartphone-based digital cup alignment guide to improve placement accuracy and provide a cost-effective and accessible solution for THA. Methods: A smartphone application for acetabular cup placement in THA using built-in gyroscope and accelerometer sensors was developed. The application calculates and displays the cup inclination angle to ensure surgical accuracy. A prospective study was conducted to verify and validate the new guide by assessing the difference between the target pre-operative planned angles and the post-operative placement angles in 87 patients. Differences between the displayed intra-operative angles and the post-operative placement angles were compared between the new guide and CT-based navigation in 20 of the 87 cases. Results: The post-operative cup inclination and anteversion angles were 40.4 ​± ​2.9° (range 35–47°) and 13.7 ​± ​4.4° (range 5–27°). Differences between the intra-operative target and post-operative cup inclination and anteversion angles were 1.8 ​± ​1.9° (range 0–7°) and 2.8 ​± ​2.5° (range 0–10°), respectively. The application demonstrated no significant difference in cup inclination and anteversion angle accuracy compared with CT-based navigation. Conclusions: The smartphone-based guide provides a practical alternative for cup placement in THA, especially in settings where CT-based navigation is not available. Challenges include the need to manage intra-operative pelvic alignment and rotational errors, which suggest room for improvement. However, it is a cost-effective and accessible tool that can improve the accuracy of acetabular cup placement in THA.